Tradisi Masyarakat Adat Jawa Terhadap Pantangan Pernikahan Di Bulan Muharam Perspektif Hukum Islam - Mardiantari, Ani; Farida, Annikmah; Dimyati, Moh.; Dwilestari, Ita; Nurkholis (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2022)
Background. Marriage is a holy, strong, and solid agreement to live together legally between a man and a woman to form an eternal family, polite, loving, peaceful, and happy.Aim. The purpose of this study was to determine the traditions of the Javanese indigenous peoples against marriage taboos in the month of Muharram from the perspective of Islamic law.Methods. This study uses field research (Field Research), using a descriptive nature that is to provide descriptions and information about marriage taboos in the month of Muharram Islamic Law Perspective in Bandar Rejo Village, Way Pengubuan District, Central Lampung Regency. And by using an empirical approach as a framework of proof or testing to ensure a truth. The data obtained through the interview method.Results. The prohibition of getting married in the month of Muharram which occurs in the village of Bandar Rejo, Way Pengubuan District, Central Lampung Regency, in Islamic law there are no specific texts, both Al-Quran and Hadith that determine a certain day as the day when marriage is prescribed. While the taboo on marrying in the month of Muharram which causes this disaster is not justified, because the calamity is a test from Allah.